Optimizing Digital Platforms as a Strategy to Improve the Skills of Creative Industry Players in MSMEs Assisted by CIC Hub Cirebon - Fariza, Muthia; Norhan , Linda; Nurkhalisha , Mustika; Mokoagow , Almira Sofia (Journal of Economics and Management Scienties, 2025)
The rapid development of the digital economy has shifted the way micro, small, and medium enterprises (MSMEs) compete, demanding the continuous improvement of human capital to remain relevant in the creative industry sector. This study aims to analyze the effect of digital platform utilization and the challenges faced on the improvement of creative industry players’ skills in MSMEs fostered by CIC Hub Cirebon. A quantitative descriptive approach was employed, using a saturated sample of 55 respondents representing the entire population. Data were collected through a structured Likert-scale questionnaire and analyzed using validity and reliability tests, as well as simple linear regression with PLS. The results show that all measurement items meet convergent and discriminant validity criteria, with composite reliability > 0.70, indicating high construct reliability. The structural model yielded an R² value of 0.324, meaning that digital platform utilization and related challenges explain 32.4% of the variance in skill improvement, with significant path coefficients (p < 0.05). These findings are consistent with Human Capital Theory and the Resource-Based View, reinforcing those digital platforms are not merely marketing channels but strategic tools for structured skill enhancement. This research contributes theoretically by integrating human capital and digital capability perspectives and practically by providing a framework and training module that can be implemented to empower MSME creative industry players to compete in the digital era.